2011
DOI: 10.1186/1476-511x-10-176
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the mechanism of low high-density lipoprotein cholesterol in obesity

Abstract: Obesity, a significant risk factor for various chronic diseases, is universally related to dyslipidemia mainly represented by decreasing high-density lipoprotein cholesterol (HDL-C), which plays an indispensible role in development of cardiovascular disease (CVD). However, the mechanisms underlying obesity and low HDL-C have not been fully elucidated. Previous studies have focused on the alteration of HDL catabolism in circulation following elevated triglyceride (TG). But recent findings suggested that liver a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 90 publications
(98 reference statements)
5
77
0
5
Order By: Relevance
“…This was expected, as obese subjects who are otherwise healthy generally exhibit this clinical phenotype. 31,32 However, at study conclusion, both cholesterol and triglyceride levels were significantly improved toward the normal range in the supplement cohort but not in placebo. Similarly, fasting glucose levels were reduced to 95 mg/dL in the treated group, whereas placebo glucose levels remained above 100 mg/dL.…”
Section: Discussionmentioning
confidence: 86%
“…This was expected, as obese subjects who are otherwise healthy generally exhibit this clinical phenotype. 31,32 However, at study conclusion, both cholesterol and triglyceride levels were significantly improved toward the normal range in the supplement cohort but not in placebo. Similarly, fasting glucose levels were reduced to 95 mg/dL in the treated group, whereas placebo glucose levels remained above 100 mg/dL.…”
Section: Discussionmentioning
confidence: 86%
“…In obese adults, adipose tissues contain over 50 % of the total cholesterol (TC) in the body. Several previous in vivo and in vitro studies provided evidence that the adipocyte cholesterol efflux to HDL was under the control of ABCA1 [2]. ABCA1 polypeptide (ENSP00000363868, O95477) has two homologous halves, and contains 2261 amino acids (254.3 kDa) [11].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has demonstrated that childhood obesity has profound effects on morbidity and mortality in adult life [1]. Obesity is associated with several co-morbid conditions, such as dyslipidemia, atherosclerosis, chronic heart disease, hypertension, stroke, diabetes mellitus, osteoarthritis, and some types of cancer [2,3]. The primary dyslipidemia related to obesity is characterized by increased circulating triglycerides (TGs), decreased highdensity lipoprotein (HDL) levels, and abnormal low-density lipoprotein (LDL) composition [4].…”
Section: Introductionmentioning
confidence: 99%
“…LCAT esterifies the absorbed cholesterol and produces cholesterol ester (CE), contributing to the formation of mature HDL, thus preventing its early renal catabolism [32] . CVID and XLA patients have a pro-inflammatory status even in the absence of acute infectious processes, which may result in reduced synthesis of apo A-I, LCAT, and ABCA1, thus leading to lower HDL-c levels [33] .…”
Section: Discussionmentioning
confidence: 99%